Studi Teoritis Derivat 4,5-Difenil Imidazol Sebagai Inhibitor Korosi Besi dengan Teori Fungsi Kerapatan (DFT) - Baari, Muhamad Jalil; Alif, Alfiah; Kurniawan, Muhammad Akbar S; Finarisnawati, Finarisnawati (Al-Kimia, 2024)
Corrosion is a severe problem in the petroleum industry. The use of corrosion inhibitors is an effort to reduce the corrosion rate on metal materials. This study used the computational chemistry approach to investigate the corrosion inhibition performances of 4,5-diphenyl imidazole and its derivatives with additional substituents, for instance, electron acceptors and electron donors. Geometry optimizations and calculations of molecular frontier orbital energies were conducted using density functional theory (DFT) in the aqueous phase. These frontier orbital energy values were used to determine other reactivity and stability parameters, such as band gap energy, electron affinity, ionization potential, chemical hardness, chemical softness, number of electron transfers, chemical potential, nucleophilicity, electrophilicity, electronegativity, back donation energy, and interaction energy. Electrostatic potential, Mulliken atomic charge, and theoretical inhibition efficiency of 4,5-diphenyl imidazole derivatives were also determined. Generally, the presence of electron donor substituents theoretically increases corrosion inhibitors. The 4,5-diphenyl imidazole with –NH2 substituent is a better derivative than others based on several reactivity and stability parameters due to adding adsorption centers. Therefore, it can increase the performance of 4,5-diphenyl imidazole as a corrosion inhibitor. The adsorption behaviors of 4,5-diphenyl imidazole and its derivatives on Fe(100) surfaces were investigated using molecular dynamics simulation. The binding energies of three types of inhibitors on the Fe surface of studied inhibitors followed the order: D–NH2 > 4,5-diphenyl imidazole (D) > D–NO2. This ranking obtained is consistent with the theoretical inhibition efficiency.